2022
DOI: 10.5187/jast.2022.e89
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbial composition changes induced by Lactobacillus plantarum GBL 16, 17 fermented feed and intestinal immune homeostasis regulation in pigs

Abstract: In this study, Rubus coreanus (R. coreanus) byproducts with high polyphenol content were fermented with R. coreanus-derived lactic acid bacteria (Lactobacillus plantarum GBL 16 and 17). Then the effect of R. coreanus-derived lactic acid bacteria fermented feed (RC-LAB fermented feed) with probiotics (Bacillus subtills, Aspergillus oryzae, Yeast) as a feed additive for pigs on the composition of intestinal microbes and the regulation of intestinal immune homeostasis was investigated. Seventy-two finishing Berks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…In addition, gut microbial modulation by Lactobacillus has a positive relationship with gut immune homeostasis and defense systems [30]. These results proposed that dietary DDGS could increase pathogenic bacteria and decrease beneficial bacteria populations; however,…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, gut microbial modulation by Lactobacillus has a positive relationship with gut immune homeostasis and defense systems [30]. These results proposed that dietary DDGS could increase pathogenic bacteria and decrease beneficial bacteria populations; however,…”
Section: Discussionmentioning
confidence: 98%
“…In accordance with this study, Mountzouris et al also demonstrated that β -galactosidase supplementation could be attributed to the increased level of the Lactobacillus population [ 29 ]. In addition, gut microbial modulation by Lactobacillus has a positive relationship with gut immune homeostasis and defense systems [ 30 ]. These results proposed that dietary DDGS could increase pathogenic bacteria and decrease beneficial bacteria populations; however, proper enzyme inclusion could reverse the population of the pathogenic and beneficial bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota's diversity is crucial, starting with its fundamental role in the digestion and absorption of nutrients. The myriad of microorganisms residing in the gastrointestinal tract play a critical role in breaking down a broad spectrum of dietary fibers and nutrients, leading to enhanced nutrient uptake and improved digestive efficiency (Yu et al, 2022;Zhong et al, 2023). This microbial diversity extends its benefits beyond digestion to bolster the immune system.…”
Section: Fimm Incubation Increased the Microbial Diversitymentioning
confidence: 99%
“…In addition, high proportions of Lactobacillus and Bifidobacterium were mainly observed in the group that consumed whey protein ( Boscaini et al, 2019 ; Boscaini et al, 2020 ; Boudry et al, 2013 ; McAllan et al, 2014 ; Schaafsma et al, 2021 ; Sprong et al, 2010 ). The combination of Lactobacillus and Bifidobacterium has been mentioned in one study as a potential candidate strain to be used for immune enhancement, thus an increase in the proportion of Lactobacillus and Bifidobacterium in the gut microbiome could potentially associated with immune enhancing effects ( Yu et al, 2022 ). In two studies by Boscaini et al comparing casein and whey protein, at the family level, the relative abundance of Streptococcaceae was higher in the casein group, and the relative abundance of Lactobacillaceae was higher in the whey protein group.…”
Section: Effects Of Dairy Products and Dairy Protein On The Gut Micro...mentioning
confidence: 99%